Phenomenology of the heating, melting and diffusion processes in Au nanoparticles - Bertoldi, Dalía Surena (2021)
The paper reports the results of a Molecular Dynamics study of the heating and melting process of nanoparticles with 1985 to 84703 atoms. Building on a previous study by the present authors [Bertoldi et al. Journal of Physics and Chemistry of Solids, 2017, 111, pp. 286-293] involving the energy versus temperature, the Lindemann index and the radial distribution function, the current work relies on the mean-square displacement, the Lindemann ratio and the simulated snapshots to characterize four regions in the process of heating-to-melting. A general pattern of the atomic configuration evolution upon heating and a systematics of the transition temperatures between the various identified steps, is proposed. In addition, the most significant, so-called “melting step” in this process is analyzed in terms of the quasi-chemical approach proposed by Bertoldi et al., which treats this step by invoking a dynamic equilibrium of the type Au (LEA-SPL) *) Au (HEA-LPL) involving low-energy atoms (LEA) and high-energy atoms (HEA) forming the solid phase-like (SPL) and the liquid phase-like (LPL) states of the system, respectively. The “melting step” is characterized by evaluating the equalGibbs energy temperature, i.e., the “T0 temperature”, previously introduced by the current authors, which is the thermodynamic counterpart of the temperature of fusion of macroscopic elemental solids. The diffusion coefficients at T0 are determined, and their spatial and temperature dependence is discussed. In particular, the activation energy for the atom movements in the HEA-LPL/LEASPL mixture at T0 is reported. The consistency between the current phenomenological picture and microscopic interpretation of the thermodynamic, kinetic and atomic configuration information obtained is highlighted.